Life and Health Protection as a Public Administration Task – Remarks Against a Background of the Act on Mass Events Security - Olejniczak-Szałowska, Ewa (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
The aim of the paper is to analyse the character of the competences of public administration organs related to life and health protection of the participants of mass events. A thesis is made that these competences (taking form of permission, order and prohibition) are legal instruments characteristic of administrative police as a function of the public administration. The necessity of collaboration of government and self-government administration organs is emphasized. The study implements the legal-dogmatic metod of research.